SOSIOLOGI LEMBAGA PENDIDIKAN: PEMBENTUKAN KARAKTER KEWIRAUSAHAAN SOSIAL SISWA MELALUI UNIT PRODUKSI DI SMK MA’ARIF NU 1 CILONGOK - Tri Ibnu Abdul Yusuf; Muh. Hanif (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This article is designed to examine the development of students’ social entrepreneurial character through production units in vocational senior high schools from the perspective of the sociology of educational institutions. The focus of the study is on the argument that production units in vocational senior high schools can foster social entrepreneurial character through practical work experience, collective responsibility, and a focus on community benefit. This issue is significant because educational institutions are not merely venues for the transmission of knowledge, but also arenas for the formation of social relations, values, compliance, identity, and life opportunities for learners. The research was designed using a qualitative field approach through observation, interviews, and documentation. The primary data is directed towards examining three empirical findings: students’ activities in production, marketing, record-keeping, and customer service; changes in students’ attitudes regarding responsibility, creativity, cooperation, and independence; and the impact of the production unit on the madrasah or the surrounding community. Conceptually, this article is grounded in social entrepreneurship, the madrasah production unit, and vocational senior high schools as analytical frameworks. The article’s contribution lies in the formulation of an empirical explanation that links the daily practices of educational institutions with broader social structures. Thus, this paper is expected to assist students in producing articles that are not merely descriptive, but analytical, argumentative, and relevant to the development of educational quality Islamic.